(untitled) (Journal of Global Accounting, 2024)
The study examined the effect of taxes on net investment of industrial goods firms in Nigeria. Specifically, it examined the effect of Company Inome Tax (CIT), Tertiary Education Tax (TET), Value Added Tax (VAT), Capital Gains Tax (CGT) and Industrial Training Tax (ITT) on Net Investment (NI). Research adopted the ex-post facto research design to study a population of thirteen (13) listed industrial goods firms over a period of 11 years (2013-2023). Data obtained were analysed using the panel regression. The results showed that company income tax and tertiary education tax had insignificant effect on net investment, though positively negatively related respectively. The study further found that value added tax and capital gains tax were negatively significant, while industrial training tax was positively significant. The study therefore concluded that except for company income tax and tertiary education tax, tax liabilities have significant effect on net investment of industrial goods firms in Nigeria. Based on these findings, the study recommended that to sustain the positive relationship between company income tax and net investment, the government should sustain the current company income tax rate, as an attempt to increase this rate may distort this relationship. Moreso, government should invest more in the overall educational demand of her citizens not only from tax revenues but from other oil and non-oil sources to reduce the burden on firms. Also, the VAT rate paid by firms should be reduced or reversed back to 5% in order to free up more cash for the firms to reinvest in the business. The companies should also be encouraged to dispose all its idle lying assets. Industrial training tax should be introduced to other sectors where not applicable. enough time to take decisions that are efficient and effective in enhancing better firm performance, as well make sure that the businesses are adherence to policies, rules, procedures code of conduct and regulations.